Design on VSPR Control Algorithm of WT2500 Wind Turbine - ZHAI Dayong; YE Wei (Kongzhi Yu Xinxi Jishu)
It firstly analyzed the affects of the main vibration modes for each part of wind turbine, including rotor, drive train and tower, and designed the control algorithms in accordance with CSR WT2500 wind turbine. Secondly, it simulated stability and dynamic performance of the controller through Bladed and Matlab. Finally, the experiment results verified the efficiency of control algorithm in site debugging, and the control parameters were optimized.